Answer:
Part 1) h(g)=-4+g ----> the input is g
Part 2) f(h)=-h-7 -----> the input is h
Part 3) g(f)=-2f -----> the input is f
Explanation:
Part 1) we have
h(g)=-4+g
we know that
The input is the independent variable and the output is the dependent variable
so
the output is h(g) or 4+g
the input is the variable g
Part 2) we have
f(h)=-h-7
we know that
The input is the independent variable and the output is the dependent variable
so
the output is f(h) or h-7
the input is the variable h
Part 3) we have
g(f)=-2f
we know that
The input is the independent variable and the output is the dependent variable
so
the output is g(f) or 2f
the input is the variable f